Pharmacodynamic and genomic markers associated with response to the XPO1/CRM1 inhibitor selinexor (KPT‐330): A report from the pediatric preclinical testing program. Issue 2 (23rd September 2015) - Attiyeh, Edward F.; Maris, John M.; Lock, Richard; Reynolds, C. Patrick; Kang, Min H.; Carol, Hernan; Gorlick, Richard; Kolb, E. Anders; Keir, Stephen T.; Wu, Jianrong; Landesman, Yosef; Shacham, Sharon; et al.
Abstract : Background: Selinexor (KPT‐330) is an inhibitor of the major nuclear export receptor, exportin 1 (XPO1, also termed chromosome region maintenance 1, CRM1) that has demonstrated activity in preclinical models and clinical activity against several solid and hematological cancers. Procedures: Selinexor was tested against the Pediatric Preclinical Testing Program (PPTP) in vitro cell line panel at concentrations from 1.0 nM to 10 μM and against the PPTP in vivo xenograft panels administered orally at a dose of 10 mg/kg thrice weekly for 4 weeks. Results: Selinexor demonstrated cytotoxic activity in vitro, with a median relative IC50 value of 123 nM (range 13.0 nM to >10 μM). Selinexor induced significant differences in event‐free survival (EFS) distribution in 29 of 38 (76%) of the evaluable solid tumor xenografts and in five of eight (63%) of the evaluable ALL xenografts. Objective responses (partial or complete responses, PR/CR) were observed for 4 of 38 solid tumor xenografts including Wilms tumor, medulloblastoma (n = 2), and ependymoma models. For the ALL panel, two of eight (25%) xenografts achieved either CR or maintained CR. Two responding xenografts had FBXW7 mutations at R465 and two had SMARCA4 mutations. Selinexor induced p53, p21, and cleaved PARP in several solid tumor models. Conclusions: Selinexor induced regression against several solid tumor and ALL xenografts and slowed tumor growth in a larger number of models. Pharmacodynamic effects for XPO1 inhibition were noted. Defining the relationship between selinexor systemic exposures in mice and humans will be important in assessing the clinical relevance of these results. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.